(untitled) (Revista Contexto & Saúde, 2022)
Hypovitaminosis D is considered a worldwide epidemic with implications that may affect the health of workers. This is a cross-sectional study conducted with 91 workers in order to assess the prevalence of hypovitaminosis D and the associations with metabolic parameters. The participants were evaluated regarding their sociodemographic and occupational profile, exposure to sunlight, anthropometric data and blood pressure. The following exams were performed: 25-hydroxyvitamin D [25(OH)D] and other metabolic parameters. There was a prevalence of 61.54% of the deficiency/insufficiency of 25(OH)D serum levels. No associations were confirmed between the vitamin D status and the sociodemographic and occupational characteristics through the Poisson regression. There was an increased prevalence in patients with diabetes and hypertriglyceridemia. Individuals with high TAC values showed a reduction in the prevalence of hypovitaminosis D. In conclusion, a high prevalence of hypovitaminosis D was found among the workers, and an increased prevalence for individuals with diabetes and hypertriglyceridemia, with TAC proving susceptible to reduce this deficiency/insufficiency. The need to monitor laboratory parameters in the health surveillance of workers is stressed.upational Health.